ANALISIS PESAN MORAL DALAM FILM “ANAK NEGRI” KARYA GATOTKOCO SUROSO - Hia, Fitri Santi (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2025)
This type of research is descriptive qualitative research. The data source is the conversation or storyline in the film "Anak Negeri" by Gatotkoco Suroso which contains a moral message. The results of this research show that the film "Anak Negeri" by Gatotkoco Suroso has a moral message about human relationships with themselves, human relationships with other humans, and human relationships with God. The moral message in this film contains teachings about human life to do good deeds. Furthermore, the moral message in the film "Anak Negeri" by Gatotokoso Suroso can be an inspiration for young people who want to pursue education and want to be successful. As children, they are taught to respect parents and discipline rules. Children are also taught to respect other people and be responsible. Suggestions that researchers can put forward are (1) the results of this research can be used as reference material for teachers to teach students about morals (2) this research should be used as a guide in finding moral messages in a film (3) future researchers should be able to develop research This has a broader scope relating to literary works.